Spatio-temporal Variability and Trends in Rainfall and Temperature in Anger watershed, Southwestern Ethiopia - Gemechu Yigezu Ofgeha; Muluneh Woldetsadik Abshire (Journal of Applied Geospatial Information, 2021)
Insights to broadly argued research gap on lack of climate studies at micro-scale considering unique features of an area, this paper intended to examine agro-ecological level spatio-temporal trends and variability in rainfall and temperature in Anger watershed of southwestern Ethiopia. The gridded data managed by the Ethiopia National Meteorological Services Agency (NMSA) for 1983-2018 were used. The Mann-Kendall test for trend analysis and different variability measures were used. Questionnaire and FGD data on community perceptions gathered from 214 households and elders were analysed descriptively and qualitatively. The study reveals the consistent increasing trends in temperature; and high variability and insignificant but increasing rainfall trend. The trends and variability show spatio-temporal differences along agro-ecologies. The watershed is characterized by moderate to high rainfall coefficient of variations, significant years of high rainfall concentration, and considerable negative annual rainfall anomalies; that the variability was severe in woinadega followed by kolla agro-ecology. Although, the perceptions on trends, variability and its implications show difference across agro-ecology, the propensity to increased temperature, unclear rainfall trend and significant inter-annual and seasonal variability were witnessed. Unpredictability of rainfall time, concentrations in kiremt, and unexpected rain during harvesting was major challenges resulting multifaceted impacts on the small-scale farmers’ livelihoods.